Espressioni Letterali

  • Materia: Espressioni Letterali
  • Visto: 2615
  • Data: 30/12/2008
  • Di: Redazione StudentVille.it

$-2(x^2y^4)^3:[(4x^3)^2(-1/2y^3)^4]+[-5/3a^2+4/3a^2b^2:(-2/3b)^2]^2:(-2a)^4$

esercizio svolto o teoria

A cura di: Francesco Speciale

Svolgimento:
$-2(x^2y^4)^3:[(4x^3)^2(-1/2y^3)^4]+[-5/3a^2+4/3a^2b^2:(-2/3b)^2]^2:(-2a)^4=$
$=-2(x^6y^(12)):[16x^6(1/(16)y^12)]+[-5/3a^2+4/3a^2b^2:(-4/9b^2)]^2:16a^4=$
$=-2x^6y^(12):[x^6y^12]+[-5/3a^2+3a^2]^2:16a^4=$
$=-2+[4/3a^2]^2:16a^4=$
$=-2+[(16)/9a^4]:16a^4=-2+1/9=-(17)/9$.